Evaluation of Traffic Sign Educational Game Based on Augmented Reality (AR) Using Marker Based - Purwanto, Dimas Yudistira; Norhikmah, Norhikmah; Mu’arif, Zidan; Muharam, Fatta (Sistemasi: Jurnal Sistem Informasi, 2025)
This study aims to develop a 3D educational game themed around traffic signs to enhance children's understanding and discipline regarding traffic rules. The research methodology includes game development using Unity and evaluation through black-box testing and questionnaires. The results show that the educational game successfully increased student interest by 80% and improved their understanding of traffic sign material, while also providing an interactive and enjoyable learning experience.